Heterogeneity of lung disease associated with NK2 homeobox 1 mutations. (August 2017) - Nattes, Elodie; Lejeune, Stephanie; Carsin, Ania; Borie, Raphael; Gibertini, Isabelle; Balinotti, Juan; Nathan, Nadia; Marchand-Adam, Sylvain; Thumerelle, Caroline; Fauroux, Brigitte; Bosdure, Emmanuelle; Houdouin, Veronique; et al.
Abstract: We retrospectively studied the clinical presentation, treatment modalities and outcome in 16 patients with heterozygous NKX2-1 mutation associated with chronic lung disease. Twelve different NKX2-1 mutations, including 4 novel mutations, were identified in the 16 patients. Nine patients presented with brain-lung-thyroid syndrome, 3 had neurological and lung symptoms and 4 had only pulmonary symptoms. Ten patients had neonatal respiratory distress, and 6 of them developed infiltrative lung disease (ILD). The other patients were diagnosed with ILD in childhood (n = 3) or in adulthood (n = 3). The median age at diagnosis was 36 months (IQ 3.5–95). Patient testing included HRCT (n = 13), BALF analysis (n = 6), lung biopsies (n = 3) and lung function tests (n = 6). Six patients required supplemental oxygen support with a median duration of 18 months (IQ 2.5–29). All symptomatic ILD patients (n = 12) benefited from a treatment consisting of steroids, azithromycin (n = 9), and/or hydroxychloroquine (n = 4). The median follow-up was 36 months (IQ 24–71.5). One patient died of respiratory failure at 18 months and another is waiting for lung transplantation. In summary, the initial diagnosis was based on clinical presentation and radiological features, but the presentation was heterogeneous. Definitive diagnosis required genetic analysis, which should be performed, even in absence of neurological or thyroid symptoms. Highlights: Sixteen subjects diagnosed with ILD associated with NKX2-1 mutations were reviewed. Four new variants were identified in 13 children and 3 adults. Lung phenotype due to NKX2-1 mutations is heterogeneous. Lung symptoms may be associated with neurological or hypothyroidism or isolated. Most of the patients progressively evolve to interstitial lung fibrosis.